MENGASUH ANAK DALAM PANDANGAN SAMIN - Sadiran Sadiran (Jurnal JPSD (Jurnal Pendidikan Sekolah Dasar), 2017)
This study uses a post-structural sociology approach i.e. ethno-methodology as a basis to attract normative behavior. Habitus Theory is used to analyze the habit of Sedulur Sikeps parent in nurturing their children, supported by the Bourdieus theory of social distinction. Habitus theory is associated with behavior, language, culture, education and art in social and cultural daily life. While social distinction is used to see and understand how each parent of Samin take a position as a teacher. The first theory is to identify the main theories of habituation behavior conducted in childcare by parents of Samin, while the second theory is a supportive theory, in order to see the extent of the influence of parents on parenting. Child-rearing theory used Thomas Lickonas theory of parenting. The research data collection was using constructive phenomenological approach, which is to find the essential meaning of the Patterns of Child Care, which includes Samins daily activities, rituals and traditions. Based on the data analysis, it is found that the parents suspicions to formal education is the fear that their children will get negative influence from their mates that consequently ignore the messages of his ancestors. In addition, they afraid if their children will be difficult to receive advise because schools do not teach behaviors. Parenting is a parental obligation that should not be delegated to teachers at school, and to become parent as well as a teacher at once for their children is human nature so does not need to learn from others. Parents to their children put permissive and openness characters forward so that in time the parents are living reminder of how well the ancestral messages such as their way of life, way of thinking, and way to get along in daily life. However, the parents will still give example in the life of the children. The parenting system is integration between the outer (lahir) and inner (batin), while the method is close-distanced communication within the family, mligi (consistently) be given little by little since childhood. When their son made a mistake, they (sons) realize it by themselves. Intervention from outer parties is not yet needed because it is difficult to get space for interaction so that social change was not able to make influences